2012
DOI: 10.1161/hypertensionaha.112.197301
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of MicroRNA-155 in Regulating Endothelium-Dependent Vasorelaxation by Targeting Endothelial Nitric Oxide Synthase

Abstract: Abstract-Nitric oxide generated by endothelial nitric oxide synthase (eNOS) plays an important role in maintaining cardiovascular homeostasis. Under various pathological conditions, abnormal expression of eNOS contributes to endothelial dysfunction and the development of cardiovascular diseases. A variety of pathological stimuli has been reported to decrease eNOS expression mainly through decreasing eNOS mRNA stability by regulating the binding of several cytosolic proteins to the cis-acting sequences within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
229
0
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(248 citation statements)
references
References 41 publications
8
229
0
11
Order By: Relevance
“…No significant differences in cell viability were detected between OGD/I, OGD/IC, OGD/M, and OGD/MC samples. Another possible regulator of the endothelial integrity, endothelial NO synthase, is directly targeted by miR‐155 16, 18. NO is involved in protection of the BBB from hypoxia/reoxygenation‐mediated injury 22.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences in cell viability were detected between OGD/I, OGD/IC, OGD/M, and OGD/MC samples. Another possible regulator of the endothelial integrity, endothelial NO synthase, is directly targeted by miR‐155 16, 18. NO is involved in protection of the BBB from hypoxia/reoxygenation‐mediated injury 22.…”
Section: Resultsmentioning
confidence: 99%
“…miR‐155 expression is limited to hematopoietic cells and cells involved in vascular remodeling, including endothelial cells 15, 16. Our previous studies demonstrated that miR‐155 negatively regulates proangiogenic signaling pathways in mouse brain endothelial cells: inhibition of miR‐155 significantly enhanced while overexpression significantly inhibited the in vitro endothelial morphogenesis 17.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this effect was attenuated by simvastatin, but the beneficial actions of the statin were abolished by co-incubation with mevalonate or GGPP. Interestingly, they were mimicked by inhibition of RhoA, suggesting that the mevalonate/ GGPP/RhoA pathway underlies the observed effects of simvastatin on miR-155 expression (103). The increased expression of eNOS mediated by statins translates into improved endothelial function, as evidenced in animal models of age-related (27) and high-fat-diet-induced (119) endothelial dysfunction.…”
Section: Effects Of Statins On Enosmentioning
confidence: 98%
“…Previous studies have demonstrated that endothelial miRNAs control endothelial functions and are implicated in the onset and development of cardiovascular disease 9,[19][20][21][22] . However, the role of endothelial miRNAs in BP homeostasis has been poorly understood.…”
Section: Discussionmentioning
confidence: 99%